Applying the WHO INSPIRE Framework to Ending Violence Against Pregnant Women and Unborn Children: A Case Study in Vietnam - Do, Huyen Phuc (Violence against women, 2025)
This article adapted the INSPIRE framework, developed by the World Health Organization to prevent violence against children, to the systematic analysis of city-level healthcare services for pregnant women who experienced intimate partner violence. A mixed-methods study conducted in-depth interviews with 22 health and social care professionals and 140 pregnant women in Vietnam. The women were more likely to report limited system-level support for partners regarding violence and mental health, while the professionals perceived more weaknesses in policies and management of services. Traditional values tend to isolate abused women from receiving social services. The INSPIRE framework is innovative and could be applied in other contexts.